2017
DOI: 10.1021/jacs.7b00427
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Four Diastereomers of Monorhamnolipids

Abstract: Rhamnolipids are amphiphilic glycolipids biosynthesized by bacteria that, due to their low toxicity and biodegradability, are potential replacements for synthetic surfactants. The previously limited access to pure materials at the gram scale has hindered extensive characterization of rhamnolipid structure-performance behavior. Here, we present an efficient and versatile synthetic methodology from which four diastereomers of the most common monorhamnolipid, α-rhamnopyranosyl-β-hydroxydecanoyl-β-hydroxydecanoate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 120 publications
(150 reference statements)
7
73
0
Order By: Relevance
“…The experimental surface area per molecule at the complete surface coverage is reported as ~117 ± 12 Å 2 . 28 There is a good agreement between the experiment and calculations, which supports the performance of the force field.…”
Section: Simulation Methodssupporting
confidence: 66%
“…The experimental surface area per molecule at the complete surface coverage is reported as ~117 ± 12 Å 2 . 28 There is a good agreement between the experiment and calculations, which supports the performance of the force field.…”
Section: Simulation Methodssupporting
confidence: 66%
“…[20,45,55,56]. Finally, because the production of both biologically synthesized and chemically synthesized [57] rhamnolipids have not been adequately evaluated at industrial scales, the economics of large-scale production should be studied to elucidate the long-term potential of rhamnolipid applications.…”
Section: Discussionmentioning
confidence: 99%
“…Pemberton et al reported that two diastereomers Rhamnolipids and their enantiomers exhibited the similar values of minimum surface tension (~28 mN/m), CMC, and aggregation behavior at pH 4, when the surfactants exist in the nonionic state. However, at pH 8 when the surfactants exits in the ionic state, the CMC and the aggregation behavior of the diastereomers and their enantiomers were somewhat different . Basically, it could be inferred that the spatial orientations of the head group is important in determining the physicochemical properties of diastereomeric surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…However, at pH 8 when the surfactants exits in the ionic state, the CMC and the aggregation behavior of the diastereomers and their enantiomers were somewhat different. 55 Basically, it could be inferred that the spatial orientations of the head group is important in determining the physicochemical properties of diastereomeric surfactants. Interestingly, the diastereomers investigated here show identical surface tension profiles, with CMC at 0.3 mM, indicating that the head groups have similar orientation at the interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation